Cover Picture: Visible‐Light‐Active Elemental Photocatalysts (ChemPhysChem 5/2013). Issue 5 (21st March 2013) - Liu, Gang; Niu, Ping; Cheng, Hui‐Ming
<x xml:space="preserve">Abstract</x> The search for visible‐light‐responsive photocatalysts has been an intensifying endeavor worldwide due to their application in solar energy conversion. Although they are not yet widely investigated as conventional compound photocatalysts, elemental semiconductors have emerged as a new and attractive class of visible‐light photocatalysts. They may open up new opportunities in developing highly active and efficient photocatalysts, as reviewed on p. 885 ff. by H.‐M. Cheng et al.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>